Inherited Antithrombin Deficiency Causing Thrombophilia - Egeberg, O (Thrombosis and Haemostasis, 1965)
Blood coagulation systems were studied in members of a family with remarkably high incidence of thrombo - embolic diseases. Thrombotic episodes most often occurred as deep venous thrombosis in the legs, with the first attack at the age of 10-25 years.Pro coagulant factor activities were found within normal variation ranges.Plasma antithrombin III (progressive antithrombin) activity was abnormally low in members with history of thrombosis and in some of their children, with an average level of about 50 per cent of normal.Heparin resistance measured with plasma heparin thrombin time was increased in members with low antithrombin III, and plasma heparin cofactor activity was decreased.The results strongly support the explanation that antithrombin III and heparin cofactor are one and the same plasma substance, and that deficiency of this antithrombin can cause a severe tendency to thrombosis.The antithrombin deficiency seems to be inherited as an autosomal dominant trait.